First report of Cryptosporidium spp. in white yaks in China - Qin, Si-Yuan (BioMed Central, 2014)
BACKGROUND: Cryptosporidium is an enteric apicomplexan parasite, which can infect yaks, leading to reduction of milk production and poor weight gain. White yak (Bos grunniens) is a unique yak breed inhabiting only in Tianzhu Tibetan Autonomous County, Gansu province, northwestern China. The objective of the present study was to molecularly determine Cryptosporidium infection and species in white yaks. FINDINGS: Seventy-six fecal samples from white yaks in Tianzhu Tibetan Autonomous County, Gansu province were collected. The small subunit ribosomal RNA (SSU rRNA) gene of each sample was amplified using nested PCR and sequenced. The Cryptosporidium species was determined by comparison of the obtained sequences with that of corresponding Cryptosporidium sequences available in GenBank by BLAST (http://www.ncbi.nlm.nih.gov/BLAST/) and phylogenetic analysis with maximum likelihood (ML) using PAUP(*). The overall prevalence of Cryptosporidium infection in white yak was 5.26% (4/76). Species identification showed C. andersoni in one sample (collected in September), and C. bovis in three samples (one collected in November and two collected in September). CONCLUSIONS: The present investigation revealed the existence of Cryptosporidium infection in white yaks in China, for the first time, and two Cryptosporidium species, namely C. andersoni and C. bovis, were identified. These findings extend the host range for Cryptosporidium spp., and also provide base-line information for further studies of molecular epidemiology and control of Cryptosporidium infection in the unique white yaks.